The language of ghosts - Fawcett, Heather (Balzer + Bray, 2020)
Exiled on the moving island Astrae after a successful coup on their family's throne, the Marchena children Julian, Noa, and Maita, "Mite," search for a way to reclaim their kingdom. Julian is the most powerful mage in the Florean Archipelago, with the ability to speak all nine of the magical languages. Unfortunately, his abilities make him prone to evil, and the target of the current ruler, Xavier Whitethorn. When Noa and her siblings learn of a plot to obtain a weapon that will destroy Julian, they vow not to let it fall into Whitethorn's hands.